2017
DOI: 10.1016/j.ipl.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Improved and simplified inapproximability for k-means

Abstract: The k-means problem consists of finding k centers in R d that minimize the sum of the squared distances of all points in an input set P from R d to their closest respective center. Awasthi et. al. recently showed that there exists a constant ε ′ > 1 such that it is NP-hard to approximate the k-means objective within a factor of c. We establish that the constant ε ′ is at least 1.0013.For a given set of points P ⊂ R d , the k-means problem consists of finding a partition of P into k clusters (C 1 , . . . , C k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 9 publications
0
67
0
Order By: Relevance
“…Their analysis also shows that no natural local search algorithm performing a fixed number of swaps can improve upon this ratio. This leads to a barrier for these techniques that are rather far away from the best-known inapproximability result which only says that it is NP-hard to approximate this problem to within a factor better than 1.0013 [20].…”
Section: Introductionmentioning
confidence: 97%
“…Their analysis also shows that no natural local search algorithm performing a fixed number of swaps can improve upon this ratio. This leads to a barrier for these techniques that are rather far away from the best-known inapproximability result which only says that it is NP-hard to approximate this problem to within a factor better than 1.0013 [20].…”
Section: Introductionmentioning
confidence: 97%
“…Dasgupta first showed that the problem is NP-Hard in large dimensions [17]. A recent work of Awasthi et al [18] showed the APX-Hardness of the k-means problem in the Euclidean metric and the inapproximability bound was recently improved to 1.0013 by Lee et al [19]. Yet, we do not know of a better approximation algorithm for the continuous version and so the best known approximation algorithm achieves a 6.47-approximation.…”
Section: Introductionmentioning
confidence: 97%
“…However, the hardness of approximation for these problems is very close to 1 and, combined with the loss induced by the embedding, this cannot lead to a hardness greater than 1.01. For example, the recent approach of Awasthi et al [18] and Lee et al [19] is a reduction from vertex cover on triangle-free graphs which introduces a direct embedding for the k-means problem. Unfortunately, the gap of the reduction is also a function of the degree of the input graph, and so requires that the instance of vertex cover has bounded degree.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the theory of clustering (and more generally, the theory of algorithms) has focused on the analysis of worst-case instances [Arya et al, 2004, Byrka et al, 2015, Charikar et al, 1999, 2001, Chen, 2008, Gonzalez, 1985, Makarychev et al, 2016. For example, it is well known the popular objective functions are provably NP-hard to optimize exactly or even approximately (APX-hard) [Gonzalez, 1985, Jain et al, 2002, Lee et al, 2017, so research has focused on finding approximation algorithms. While this perspective has led to many elegant approximation algorithms and lower bounds for worst-case instances, it is often overly pessimistic of an algorithm's performance on "typical" instances or real world instances.…”
Section: Introductionmentioning
confidence: 99%